827Early life influences on timing of menarche in racial/ethnic minority and immigrant women. (2nd September 2021) - April-Sanders, Ayana; Tehranifar, Parisa; Argov, Erica Lee; Suglia, Shakira; McDonald, Jasmine
Abstract: Background: Early life adversity and infections may theoretically affect the timing and effort of reproductive development. We examined associations of childhood adversity and exposure to tonsillitis with age at menarche in women age 40-64 years. Methods: A multi-ethnic cohort of 394 women reported on exposure to parental maltreatment and maladjustment during childhood (<18 years) and on any diagnosis of tonsillitis, an infection primarily acquired in early life and adolescence. We used linear and logistic regression models to examine the associations of cumulative/specific childhood adversity experience(s) and history of tonsillitis with average age at menarche and early onset of menarche (<12 years of age). Results: The average age at menarche was 12.6 years, and was significantly lower for women who lived with a mentally ill caregiver (M = 12.4 (95% CI: 11.7-13.0)) and those with a history of tonsillitis (M = 12.6 (95% CI: 12.0-13.2)). In adjusted multivariable models, living with a mentally ill caretaker (RR = 1.5, 95% CI: 1.0-2.1) and a having a history of tonsillitis (RR = 1.7, 95% CI: 1.3-2.4) were associated with increased risk of early menarche compared with women without these exposures. Cumulative and other specific adversities were not statistically associated with early menarche. Conclusions: These findings support growing evidence that early life experiences may influence reproductive development. Key messages: Early life adversity related to living with mentally ill caretakers and a history of tonsillitis is associated with earlier menarche in racial/ethnic minority and immigrant women.